Biosorption of heavy metal by thermotolerant polymerproducing bacterial cells and the bioflocculant - Saithong Kaewchai (Songklanakarin Journal of Science and Technology (SJST), 2002)
Three strains of thermotolerant polymer-producing bacteria; Bacillus subtilis WD 90, Bacillus subtilis SM 29, and Enterobacter agglomerans SM 38 as well as their biofloculants were used to investigate on the adsorption of heavy metal, nickel and cadmium. The effects of pH and concentrations of heavy metal were investigated. The optimum pH for nickel and cadmium adsorption by the dried cells of E. agglomerans SM 38 were found to be 7.0 (25.5% removal) and 8.0 (32% removal), respectively. For B. subtilis WD 90 and B. subtilis SM 29, the optimum pH at 8.0 exhibited the nickel removal of 27% and 25%, respectively, and cadmium removal of 28% and 28.5%, respectively. The heavy metal adsorption by the dried cells and wet cells of E. agglomerans SM 38 were slightly increased with increasing initial concentrations of nickel and cadmium up to 60 and 30 ppm, respectively. The bioflocculant of B. subtilis WD 90 and B. subtilis SM 29 showed the highest nickel removal of 90.7% and 87.0% respectively, while the cadmium removal was 90.9 and 91.4%, respectively. The optimum pH for adsorption of both nickel and cadmium by the bioflocculant of E. agglomerans SM 38 was 7.0 with the removal of 92.8 and 84.2%, respectively. The optimum nickel concentration for adsorption by the bioflocculant of E. agglomerans SM 38 was 10 ppm, with the removal of 92.5%, and rather stable up to 60 ppm. The optimum cadmium concentration for adsorption by the bioflocculant of B. subtilis SM 29 was 60 ppm at pH 8.0 with the removal of 85.7%. Therefore, the bioflocculant of the three isolates gave higher heavy metal adsorption than the cells.